(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
In this paper are described and illustrated Pteropoda coming frorn two Lower Miocene sections exposed near the village of Castelsardo (Norhern Sardinia). The sampled sections cover a stratigraphic range which extends from the basal part of zone N4 to uppermost N6 (after Blow’s planktonic foraminiferal zonation), that means an Aquitaman—Burdigalian age.